2012
DOI: 10.1682/jrrd.2011.05.0090
|View full text |Cite
|
Sign up to set email alerts
|

Subjective visual vertical perception and sense of smell in Parkinson disease

Abstract: Abstract-Thisarticle describes an open cross-sectional observational study involving 47 participants with Parkinson disease (PD) and 47 (age-and sex-matched) nondisabled controls without PD. The aim was to determine the profiles of subjective visual vertical (SVV) perception and sense of smell perception in both groups. There was a statistically significant difference (p < 0.001) between patients and controls on their smell test performance. Controls were more likely to correctly identify odors, with a median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…This interpretation receives support from the small iSDs that many of these subjects exhibited, indicating that they were accurately matching the frame angle. A similar clustering of errors around the frame angle has been reported in some elderly subjects [21].…”
Section: Discussionsupporting
confidence: 84%
“…This interpretation receives support from the small iSDs that many of these subjects exhibited, indicating that they were accurately matching the frame angle. A similar clustering of errors around the frame angle has been reported in some elderly subjects [21].…”
Section: Discussionsupporting
confidence: 84%
“…The increased intraindividual variability in rod alignment for SCZ during orientation modulation of visual vertical, in comparison to controls, was greater than the resolution of the recording system (0.50°) and may indicate a clinically functional difference. Increased variability in rod alignment on the RFT has previously been reported in studies on neck pain ( 17 , 18 ), diabetes ( 19 ) and Parkinson’s disease ( 20 ), and may be a general indicator of neurological malfunction ( 21 ). Variability-related results in this study also reveal that there is a subgroup (about 50%) of SCZ who exceeded the upper limit for the reference range of control variability values (Mean + 2SD), having a mean greater by one degree than 2SD of the corresponding control value, indicating that SCZ who fell in this category were inconsistently aligning the rod relative to the frame.…”
Section: Discussionmentioning
confidence: 72%
“…These studies suggest that people with PD become reliant on vision for gait (Azulay et al, 1999;Azulay et al, 2002;Khattab et al, 2012). However many previous studies have involved visual occlusion (e.g.…”
Section: Vision and Gaitmentioning
confidence: 99%
“…Selective gait impairments are associated with deficits in visual functions (Moes and Lombardi, 2009), and exacerbated by visual manipulation in PD (Cowie et al, 2012). Studies have shown that visual functions contribute to gait control in PD (Azulay et al, 1999;Azulay et al, 2002;Khattab et al, 2012).…”
Section: Introductionmentioning
confidence: 99%